2020
DOI: 10.1017/s003118202000133x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ecological opportunity in shaping host–parasite networks

Abstract: Despite the great interest to quantify the structure of host–parasite interaction networks, the real influence of some factors such as taxonomy, host body size and ecological opportunity remains poorly understood. In this paper, we investigate the general patterns of organization and structure of interactions in two anuran–parasite networks in the Brazilian Pantanal (seasonally flooded environment) and Atlantic Forest (non-flooded forest). We present theoretical models to test whether the structures of these h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Future avenues of research should explore the extent to which host shifts, host‐range expansions, and host recolonisations characterise the evolution of other networks of intimate interactions. Given the support for the oscillation hypothesis from a variety of systems such as polyphagous moths (Wang et al, 2017), parasites (D'Bastiani et al, 2020; Hoberg & Brooks, 2008), and even plant‐microbial mutualism (Torres‐Martfnez et al, 2021), we expect similar dynamics to be found in many systems, ranging from parasitisms to mutualisms.…”
Section: Discussionmentioning
confidence: 76%
“…Future avenues of research should explore the extent to which host shifts, host‐range expansions, and host recolonisations characterise the evolution of other networks of intimate interactions. Given the support for the oscillation hypothesis from a variety of systems such as polyphagous moths (Wang et al, 2017), parasites (D'Bastiani et al, 2020; Hoberg & Brooks, 2008), and even plant‐microbial mutualism (Torres‐Martfnez et al, 2021), we expect similar dynamics to be found in many systems, ranging from parasitisms to mutualisms.…”
Section: Discussionmentioning
confidence: 76%
“…Future avenues of research should explore the extent to which host shifts, host-range expansions, and host recolonizations characterize the evolution of other networks of intimate interactions. Given the support for the oscillation hypothesis from a variety of systems such as polyphagous moths (Wang et al 2017), parasites (Hoberg and Brooks 2008; D’Bastiani et al 2020), and even plant-microbial mutualism (Torres-Martínez et al 2021), we expect similar dynamics to be found in many systems, ranging from parasitisms to mutualisms.…”
Section: Discussionmentioning
confidence: 97%
“…If we want to predict the outcomes of such complex processes, it is necessary to take the species' initial abilities (compatibility) into account and explicitly investigate how these interact with new ecological opportunities that may emerge as a result of changes in community composition and host availability. In other words, it is important to understand if an absence of interaction is caused by mismatching compatibility or lack of opportunity (Brooks et al ., 2019; D'Bastiani et al ., 2020). It is also worth noting that ‘opportunity’ here is not merely availability in the direct sense (as in co‐occurrence), but also includes the role of other ecological interactions, such as with competitors or natural enemies, which may affect the suitability of a plant as a viable host.…”
Section: Mechanisms Of Changementioning
confidence: 99%